Pengaruh Financial Technology dan Financial Knowledge terhadap Financial Behavior Generasi Milenial di Dusun Tegal Ombo: Penelitian - Raseta Mardiana; Muhammad Arif Liputo; Sahara (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
A study has been conducted to examine the influence of financial technology and financial knowledge on the financial behavior of the millennial generation in Dusun Tegal Ombo. This research employs a quantitative method with a descriptive approach and an ex post facto design. The population consists of the millennial generation in Dusun Tegal Ombo, with a sample size of 110 respondents selected using total sampling techniques. The research instrument was a questionnaire, and data analysis was performed using SPSS version 25. The findings reveal that both financial technology and financial knowledge significantly affect the financial behavior of millennials in Dusun Tegal Ombo. This is evidenced by (1) the positive and significant effect of financial technology on financial behavior, indicated by a t-statistic value greater than the t-table (3.661 > 1.659). (2) There is a positive and significant influence of financial knowledge on financial behavior, based on a t-statistic value greater than the t-table (3.566 > 1.659). (3) Additionally, both financial technology and financial knowledge positively and significantly influence financial behavior, as shown by the f-count value exceeding the f-table (23.932 > 3.08). A determination value of 30.9% was obtained.